Palaeomagnetism of the Mesozoic Serra Geral Formation, southern Brazil - Ernesto, M.; Pacca, I. G.; Hiodo, F. Y.; Nardy, A. J R [UNESP] (Elsevier, 1990)
Palaeomagnetic results from 20 volcanic sequences and 11 intrusive bodies (sills and dykes) of the Serra Geral Formation (Paraná Basin) are reported in this paper. The sequences are widespread all over the basin, while sills and dykes (Ponta Grossa arch) come from the northeastern portion. Three mean palaeomagnetic poles were computed for the Serra Geral Formation, which account for a time interval of ∼ 15 Ma. Pole SG1 is located at 85°S,108°E (α95 = 1.1°, N = 18) and represents the main phase of the magmatic activity in the basin, with a mean age of ∼ 135 Ma. Pole SG2 is located at 82°S,38°E (α95 = 7.8°, N = 2) and represents a younger magmatic phase, with an associated age of ∼ 130 Ma. Pole SG3 (72°S,37°E; α95 = 6.8°, N = 10) is the youngest pole. It is computed from the intrusive rocks and its age is assumed to be not younger than 118 Ma, the lower limit of the 'Cretaceous normal magnetic interval'. These three poles describe a shifting path, which suggest that the South American platform moved ∼ 5° southwards and rotated ∼ 10° clockwise during the Lower Cretaceous, preceding the South Atlantic opening. © 1990.
Keywords: Cretaceous; palaeomagnetism; palaeopole; Brazil, Parana Basin